Identity, Polarity and Redemption in State’s secession: The Essence of Sudan and South Sudan’s Divorce. (Hekima Review, 2020)
This article investigates the essence of identity, polarity and redemption in the secession of South Sudan from Sudan. Since there were many factors involved in triggering the Sudan and the South Sudan conflict, this paper has examined four factors which have led to the secession of South Sudan. The key issues shown by the study in both conflicts were the tribal dominance, marginalization of political elites, desire for self-governance and autonomy, inappropriate allocation of national resources, appointment into government senior position in civil services and the military. Therefore, since all the factors that triggered the Sudan conflicts encouraged people of South Sudan to fight for secession, the study concluded that the ethnic identity, polarization could be the best avenues for redeeming people from marginalization.